Effect of wing deformation on the aerodynamic performance of flapping wings: fluid-structure interaction approach - Fairuz, Z. M.; Abdullah, M. Z.; Zuber, Mohammad; Mujeebu, Muhammad Abdul; Abdullah @ Harun, Muhammad Khalil; Yusoff, H.; Abdul Aziz, M. S. (American Society of Civil Engineers, 2016)
Wing stiffness is very crucial in augmenting aerodynamic forces in flapping wing flyers. In this work, the effect of wing deformation was studied using three-dimensional numerical analysis (two-way fluid structure interaction), coupling the flow solver (FLUENT) and the structural (ABAQUS) solver via the MpCCI platform. Three different degrees of bending stiffness corresponding to rigid, flexible, and highly flexible case wings were investigated. Moreover, the wings were tested for both low Reynolds number (R=9,000) and high Reynolds number (R=40,000), at a flapping frequency of 9 Hz corresponding to an angle of attack (AoA) ranging from α=0 to 50°. The results of mean aerodynamic lift and drag coefficients showed good agreement between numerical and experimental findings. Also, the time-averaged lift-to-drag ratio reveals that the highly flexible wing exhibited the best overall aerodynamic performance when compared to the rigid and flexible wing.